2022
DOI: 10.3233/xst-221151
|View full text |Cite
|
Sign up to set email alerts
|

An interpretable multi-task system for clinically applicable COVID-19 diagnosis using CXR

Abstract: BACKGROUND: With the emergence of continuously mutating variants of coronavirus, it is urgent to develop a deep learning model for automatic COVID-19 diagnosis at early stages from chest X-ray images. Since laboratory testing is time-consuming and requires trained laboratory personal, diagnosis using chest X-ray (CXR) is a befitting option. OBJECTIVE: In this study, we proposed an interpretable multi-task system for automatic lung detection and COVID-19 screening in chest X-rays to find an alternate method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The entry of the SARS-CoV-2 virus into the respiratory system and the subsequent initiation of a strong inflammatory response lead to the breakdown of the alveolar-capillary barrier [37]. In the acute stage of infection, ARDS causes lung damage that includes the formation of hyaline membranes in the alveoli, followed by interstitial expansion, edema, and fibroblast proliferation with typical pathological changes characterized by diffuse alveolar parenchymal damage [38]. The accumulation of protein-rich fluid in the alveolar and interstitial spaces causes pulmonary surfactant inhibition [35].…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…The entry of the SARS-CoV-2 virus into the respiratory system and the subsequent initiation of a strong inflammatory response lead to the breakdown of the alveolar-capillary barrier [37]. In the acute stage of infection, ARDS causes lung damage that includes the formation of hyaline membranes in the alveoli, followed by interstitial expansion, edema, and fibroblast proliferation with typical pathological changes characterized by diffuse alveolar parenchymal damage [38]. The accumulation of protein-rich fluid in the alveolar and interstitial spaces causes pulmonary surfactant inhibition [35].…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Artificial Intelligence (AI) models, medical experience, and image research may have the energy to produce a beneficial, lasting effect on people's lives in a relatively small-time span. The analysis by computer and medical image analysis includes image recovery, image processing, image study, and image-based envision [10]. The medicalimage analysis has heightened to incorporate computer vision, pattern-identification, image-separation, and machine learning (ML) in many dimensions [ 12].…”
Section: Deep Learning In Medical Areamentioning
confidence: 99%
“…Recently, in developing CAD schemes of medical images, deep learning (DL) models have been well recognized and widely used to perform the tasks of segmenting the disease-infected regions of interest (ROIs) [ 7 , 8 ] and detecting or classifying diseases using the automatically extracted image features [ 9 , 10 ]. In using COVID-19 image datasets to develop CAD schemes, most of the previous studies focused on developing DL models to detect COVID-19 cases or classify between the COVID-19 and normal or other types of pneumonia cases [ 11 , 12 , 13 , 14 ]. Although many previous studies reported the extremely high accuracy of using DL models to detect and/or classify the COVID-19 infected cases (i.e., ranging from 90–100% accuracy [ 15 ]), no previous DL model is robust and clinically acceptable due to training bias and a “black-box” type approach [ 16 ].…”
Section: Introductionmentioning
confidence: 99%